A review of TRPM6 rs2274924 polymorphism and magnesium deficiency: Genetic–nutritional interaction in type 2 diabetes mellitus - Arini Noor Khasanah (Journal of Health and Therapy, 2025)
The Transient Receptor Potential Melastatin 6 (TRPM6) gene plays a central role in intestinal magnesium absorption and renal reabsorption. Genetic polymorphisms in TRPM6, particularly rs2274924, have been linked to altered magnesium transport, hypomagnesemia, and increased susceptibility to type 2 diabetes mellitus (T2DM). This narrative review synthesizes current findings on the interaction between TRPM6 genetic variants and dietary magnesium in relation to glucose regulation and insulin resistance. A structured literature search was conducted in PubMed, Scopus, and Web of Science to identify observational and interventional studies exploring TRPM6 polymorphisms, magnesium status, and metabolic outcomes. Evidence consistently shows that magnesium is essential for enzymatic processes in glycolysis, ATP production, and insulin secretion, and that deficiency impairs β-cell function, glucose uptake, and insulin signaling. Several studies indicate that individuals—particularly women—harboring the rs2274924 variant may exhibit greater metabolic vulnerability when habitual magnesium intake is insufficient, while adequate intake appears to reduce this genetic risk. By summarizing evidence across molecular, nutritional, and clinical perspectives, this review highlights the importance of TRPM6–magnesium interactions and their potential implications for personalized nutrition and diabetes prevention strategies.